An Incidental Learning Method to Improve Face-Name Memory in Older Adults With Amnestic Mild Cognitive Impairment. (22nd October 2020) - Biss, Renée K.; Rowe, Gillian; Hasher, Lynn; Murphy, Kelly J.
Abstract : Objective: Forgetting names is a common memory concern for people with amnestic mild cognitive impairment (aMCI) and is related to explicit memory deficits and pathological changes in the medial temporal lobes at the early stages of Alzheimer's disease (AD). In the current experiment, we tested a unique method to improve memory for face–name associations in people with aMCI involving incidental rehearsal of face–name pairs. Method: Older adults with aMCI and age- and education-matched controls learned 24 face–name pairs and were tested via immediate cued recall with faces as cues for associated names. During a 25- to 30-min retention interval, 10 of the face–name pairs reappeared as a quarter of the items on a seemingly unrelated 1-back task on faces, with the superimposed names irrelevant to the task. After the delay, surprise delayed cued recall and forced-choice associative recognition tests were administered for the face–name pairs. Results: Both groups showed reduced forgetting of the names that repeated as distraction and enhanced recollection of these pairs. Conclusions: The results demonstrate that passive methods to prompt automatic retrieval of associations may hold promise as interventions for people with early signs of AD.